Pembiasaan Kegiatan Baris-Berbaris dalam Pembentukan Nilai Pendidikan Karakter Disiplin Siswa Kelas 2 SD Negeri 1 Kutosari - Ratna Arum Sari; Wahyudi Wahyudi; Muhamad Chamdani (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2020)
Habit formed character, for instance: the habit of lining-up. The study aimed to describe the habit of lining up and to describe the habit of lining up to form discipline character. It was qualitative with a narrative approach. The procedures of the study were: 1) doing observation, 2) analyzing problem, 3) having problem statement, 4) doing research, 5) analyzing data, and 6) having data validity. The result showed that the habit of lining up in SD Negeri 1 Kutosari worked well. It was proven by some indicators: (1) precise movement based on the rules, (2) firmness of leader when giving command, (3) neatness in lining up, (4) consistency in lining up, (5) enthusiasm in lining up, (6) resemblance of movement. The lining up applied every morning in all grades. The second grade students of SD Negeri 1 Kutosari had discipline character. They showed several indicators: (1) arrived on time, (2) paid attention to the lesson, (3) did the homework, (4) obeyed school rules, (5) obeyed teacher's advice, (6) wore school uniform, and (7) had flag ceremony quietly.Keywords: Habit, Lining up, Discipline